2011
DOI: 10.1103/physrevb.84.140509
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity in pseudogapped superconductors: A sum-rule-consistent preformed-pair scenario

Abstract: We calculate the dc conductivity σ in a pseudogapped high Tc s perconductor within a precursor superconductivity theory which is consistent with gauge invariance. Our results contain physical effects beyond those identified previously. Rather than presuming that lifetime effects dominate the T dependence of transport, here we show (consistent with growing experimental support) that the temperature dependence of the effective carrier number is a natural consequence of the pseudogap, and demonstrate reasonable a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…We restrict calculations to T > T c so as to avoid complications from collective modes in the presence of pseudogap effects. We can similarly address the quasi-particle interference pattern 13,14 of STM, as well as the complex conductivity and diamagnetic susceptibility, [15][16][17][18] all of which are given in the Supplementary Materials.…”
mentioning
confidence: 99%
“…We restrict calculations to T > T c so as to avoid complications from collective modes in the presence of pseudogap effects. We can similarly address the quasi-particle interference pattern 13,14 of STM, as well as the complex conductivity and diamagnetic susceptibility, [15][16][17][18] all of which are given in the Supplementary Materials.…”
mentioning
confidence: 99%
“…Similar fluctuation effects have been also reported for the thin samples of the strongly disordered s-wave superconductors * Electronic address: doman@kft.umcs.lublin.pl [18]. These physical processes have been studied within the diagrammatic approximation for the current-current response function, using the dressed single particle propagators [19][20][21], imposing the selfconsistent conserving scheme [22] or inventing other sophisticated methods for the vertex corrections [23,24].…”
Section: Introductionmentioning
confidence: 66%
“…Moreover, an unphysical normal-state Meissner effect ensues, which implies a finite superfluid density above T c . This Comment is intended to emphasize the key role played by sum rules and other conservation constraints in transport and scattering theories of Fermi gases, as we have repeatedly stressed in our papers [3][4][5][6][7]. As pointed out in textbooks [8], it is difficult using approximate methods to obtain the same answer for the compressibility from the static correlation function and the thermodynamic derivative.…”
mentioning
confidence: 97%
“…We confine our attention in this Comment to the attractive interaction regime which was considered by us in earlier work [3][4][5][6][7] to address a systematic theory of spin and charge linear response above and below T c . Our work, not cited by the authors, was shown to be demonstrably consistent with a number of sum rules, reflecting gauge invariance.…”
mentioning
confidence: 99%